Hubungan Lingkungan Keluarga dan Penggunaan Media Sosial dengan Sikap Toleransi pada Siswa Sekolah Menengah Atas - Rusdiana, Aviana Trisepti; Al Atok, A. Rosyid (Universitas Negeri Malang, 2024)
The purpose of this study is to analyze the relationship between family environment and social media use with students' tolerance attitudes. This study used a quantitative approach with a descriptive correlational type. Family environment and social media use have a significant relationship with students' tolerance attitudes. Family environment with indicators of how parents educate, home atmosphere, and cultural background as a whole produces α 0.05 and α